2004
DOI: 10.1210/jc.2003-031488
|View full text |Cite
|
Sign up to set email alerts
|

BRAF T1796A Transversion Mutation in Various Thyroid Neoplasms

Abstract: A high prevalence of activating mutation of the B type Raf kinase (BRAF) gene was recently reported in papillary thyroid cancer (PTC). However, the frequency of this mutation in several other types of thyroid neoplasms was not thoroughly investigated. In the present study, in addition to PTC, we evaluated various thyroid tumor types for the most common BRAF T1796A mutation by direct genomic DNA sequencing. We found a high and similar frequency (45%) of the BRAF T1796A mutation in two geographically distinct PT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
76
0
6

Year Published

2005
2005
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(88 citation statements)
references
References 19 publications
(28 reference statements)
6
76
0
6
Order By: Relevance
“…Similarly, the BRAF V600E mutation has been frequently found in microcarcinomas of the thyroid (30), which suggests a role in tumor initiation rather than tumor progression. On the other hand, BRAF mutations are also found in poorly differentiated and anaplastic thyroid carcinomas, suggesting that they may play a role in their highly aggressive behavior (7,11,39,40). In the study of Nikiforova et al (7), all BRAF-mutant poorly differentiated and anaplastic carcinomas contained areas of preexisting papillary carcinoma, and the BRAF V600E mutation was present in both the well-differentiated and dedifferentiated components, suggesting that it may have contributed to the transition from PTC to anaplastic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the BRAF V600E mutation has been frequently found in microcarcinomas of the thyroid (30), which suggests a role in tumor initiation rather than tumor progression. On the other hand, BRAF mutations are also found in poorly differentiated and anaplastic thyroid carcinomas, suggesting that they may play a role in their highly aggressive behavior (7,11,39,40). In the study of Nikiforova et al (7), all BRAF-mutant poorly differentiated and anaplastic carcinomas contained areas of preexisting papillary carcinoma, and the BRAF V600E mutation was present in both the well-differentiated and dedifferentiated components, suggesting that it may have contributed to the transition from PTC to anaplastic carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16][20][21][22] This variability is due in large part to the heterogeneous nature of tumors encompassed under the designation of papillary thyroid carcinoma, and likely reflects differences in: (1) phenotypic subtypes of papillary thyroid carcinoma, (2) exposure profiles, and (3) other yet undefined population-based characteristics such as patient age. We found, for example, that when the study sample is narrowed to sporadic conventional papillary thyroid carcinomas from adult patients over the age of 60, the prevalence of BRAF mutations approaches 90%.…”
Section: Discussionmentioning
confidence: 99%
“…When multi-step carcinogenesis is taken into account, a considerable number of anaplastic carcinomas with BRAF mutations should be found. In previous reports, however, the frequency of the BRAF mutation was only about 10% on average and ranged from 0 to 63% (Fukushima et al, 2003;Namba et al, 2003;Nikiforova et al, 2003;Begum et al, 2004;Soares et al, 2004;Xing et al, 2004;Quiros et al, 2005). Among these studies, some reported that the BRAF mutation is found frequently only in anaplastic carcinomas with a papillary carcinoma component, although these studies have examined only four or five cases.…”
mentioning
confidence: 94%